Validity of the tritiated thymidine method for estimating bacterial growth rates: measurement of isotope dilution during DNA synthesis. - Pollard, P C (1984)
The rate of tritiated thymidine incorporation into DNA was used to estimate bacterial growth rates in aquatic environments. To be accurate, the calculation of growth rates has to include a factor for the dilution of isotope before incorporation. The validity of an isotope dilution analysis to determine this factor was verified in experiments reported here with cultures of a marine bacterium growing in a chemostat. Growth rates calculated from data on chemostat dilution rates and cell density agreed well with rates calculated by tritiated thymidine incorporation into DNA and isotope dilution analysis. With sufficiently high concentrations of exogenous thymidine, de novo synthesis of deoxythymidine monophosphate was inhibited, thereby preventing the endogenous dilution of isotope. The thymidine technique was also shown to be useful for measuring growth rates of mixed suspensions of bacteria growing anaerobically. Thymidine was incorporated into the DNA of a range of marine pseudomonads that were investigated. Three species did not take up thymidine. The common marine cyanobacterium Synechococcus species did not incorporate thymidine into DNA.